Efficiency of using herbal immunomodulating drug for non-specific prevention of acute respiratory infections - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2018)
A study of 68 children aged 4 to 11 years showed that the application of BNO 1030 extract in the pre-epidemic period reduces the risk of acute respiratory infections. After the preventive use of BNO 1030 extract, subsequent acute respiratory infections are characterized by a mild and uncomplicated course, which usually does not require the prescription of antibiotic therapy. It has been established that BNO 1030 extract has an anti-inflammatory effect by increasing the production of the CD14 molecule and suppressing the activity of the NF-kB transcription factor.